2012
DOI: 10.1371/journal.pone.0044289
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Pseudomonas aeruginosa Biofilms by Atmospheric Pressure Non-Thermal Plasma

Abstract: Bacteria exist, in most environments, as complex, organised communities of sessile cells embedded within a matrix of self-produced, hydrated extracellular polymeric substances known as biofilms. Bacterial biofilms represent a ubiquitous and predominant cause of both chronic infections and infections associated with the use of indwelling medical devices such as catheters and prostheses. Such infections typically exhibit significantly enhanced tolerance to antimicrobial, biocidal and immunological challenge. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(130 citation statements)
references
References 61 publications
7
116
0
2
Order By: Relevance
“…27,41 According to the results obtained from the XTT assay, even after extended treatment time of 300 s, an average of 30% of cells in biofilms were still metabolically active. This outcome was also observed by Alkawareek et al, 42 who reported that ACP inactivated 85% of P. aeruginosa cells according to colony counts, while the XTT absorbance value corresponded to 36%. Borges et al 42 observed similar bacterial response to stress, when P. aeruginosa biofilm was subjected to naturally derived compounds with 30% of cell metabolic activity remaining after the treatment.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…27,41 According to the results obtained from the XTT assay, even after extended treatment time of 300 s, an average of 30% of cells in biofilms were still metabolically active. This outcome was also observed by Alkawareek et al, 42 who reported that ACP inactivated 85% of P. aeruginosa cells according to colony counts, while the XTT absorbance value corresponded to 36%. Borges et al 42 observed similar bacterial response to stress, when P. aeruginosa biofilm was subjected to naturally derived compounds with 30% of cell metabolic activity remaining after the treatment.…”
Section: Discussionsupporting
confidence: 82%
“…This outcome was also observed by Alkawareek et al, 42 who reported that ACP inactivated 85% of P. aeruginosa cells according to colony counts, while the XTT absorbance value corresponded to 36%. Borges et al 42 observed similar bacterial response to stress, when P. aeruginosa biofilm was subjected to naturally derived compounds with 30% of cell metabolic activity remaining after the treatment. In general, the plate count assay accounts only for culturable bacterial cells and does not take into account cells that might still be metabolically active.…”
Section: Discussionsupporting
confidence: 82%
“…In previous studies using a plasma system based on a 99.5% helium, 0.05% oxygen feed gas, Alkawareek and others (Alkawareek et al, 2012), a 15 s treatment reduced Pseudomonas aeruginosa biofilms by 0.8 cfu/ml at a pulse frequency of 20 kHz and by 1.6 log cfu/ml at 40 kHz. In contrast, Niemira et al (Niemira et al, 2014), using the same equipment and feed gas (air) used in the present study, showed no clear association of antimicrobial efficacy against Salmonella biofilms for pulse frequencies ranging from 24 to 48 kHz.…”
Section: Resultsmentioning
confidence: 86%
“…A flow of feed gas (dried air) at 60 psi drives the plasma arc outward from the surrounding Teflon cowling, expanding and cooling it. Varying the pulse frequency is known to be a factor in the antimicrobial efficacy of cold plasma (Alkawareek et al, 2012). Frequencies ranging from 23 to 48 kHz were evaluated, with power consumption of 522 to 549 W.…”
Section: Cold Plasma Treatmentmentioning
confidence: 99%
“…As an antimicrobial strategy, the advantages of non-thermal plasmas operated at atmospheric pressure are the simple design, low cost of construction/operation, usage of nontoxic gases, with operating conditions of gas at or near room temperature, and no harmful residues (Gaunt et al, 2006;Kong et al, 2009;Laroussi, 2002). In last years, much effort and progress have been done in order to elucidate the exact mechanisms leading to bacterial or fungal inactivation by the action of electric plasma (Alkawareek et al, 2012;Chen et al, 2014;Laroussi, 2002;Mai-Prochnow et al, 2014;Taghizadeh et al, 2015;Traba and Liang, 2015). It is considered that several plasma products play an important role in this process, namely reactive oxygen species (ROS), such as ozone, atomic oxygen, superoxide, hydrogen peroxide and hydroxyl radicals (Kong et al, 2009), and reactive nitrogen species (RNS), UV radiation, and charged particles (Gaunt et al, 2006;Laroussi and Leipold, 2004;Ma et al, 2008).…”
Section: Introductionmentioning
confidence: 99%